Early polarization observations of the optical emission of gamma-ray bursts: GRB 150301B and GRB 150413A - Gorbovskoy, E.S. (2016)
We report early optical linear polarization observations of two gamma-ray burstsmade with the MASTER robotic telescope network. We found the minimum polarization for GRB 150301B to be 8 per cent at the beginning of the initial stage, whereas we detected no polarization for GRB 150413A either at the rising branch or after the burst reached the power-law afterglow stage. This is the earliest measurement of the polarization (in cosmological rest frame) of gamma-ray bursts. The primary intent of the paper is to discover optical emission and publish extremely rare (unique) high-quality light curves of the prompt optical emission of gammaray bursts during the non-monotonic stage of their evolution. We report that our team has discovered the optical counterpart of one of the bursts, GRB 150413A.